PENGARUH PENGGUNAAN TEKNIK MIND MAPPING TERHADAP KETERAMPILAN BERBICARA - Ermawati Arief, Silvia Hariani, Atmazaki, (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This research aims to describe the effect of the use mind mapping technique, toward students’ ability in speaking at SMP Negeri 16 Padang. The type of this research is quantitative research done using experimental design. There are three results of the research are (1) the students’ ability in speaking without using mind mapping technique at SMP Negeri 16 Padang is low and grades LdC with average 66.78, (2) the students’ ability in speaking with using mind mapping technique at SMP Negeri 16 Padang is high and grades B with average 81.78, and (3) based on t-test, alternative hypothesis (H1) is gained at the significant phase 5% and degrees of freedom (df) = (n1+n2)-2 because tcount> ttable (7,23 > 1,71). Kata kunci: pengaruh, teknik mind mapping, keterampilan berbicara